Integrasi Nilai Tauhid Dalam Filsafat Pendidikan Islam - Nur Hari Kuncara; Uswatun Suciati; Hani Aufaa Khairunnisa; Khoiriyah (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2026)
Tauhid, as the core principle of Islam, forms the foundation of Islamic educational philosophy, guiding the holistic development of human beings. This study examines the integration of tauhid within the ontological, epistemological, and axiological dimensions of education. Ontologically, tauhid positions humans as multidimensional beings with intellectual, spiritual, and moral capacities, responsible for serving Allah and fulfilling their existential purpose. Epistemologically, it integrates revelation, reason, and empirical experience, ensuring knowledge is not value-neutral but directed toward ethical and spiritual ends. Axiologically, tauhid emphasizes moral, social, and spiritual values, orienting education toward character formation and human well-being rather than mere academic achievement. Using a qualitative literature review, this study analyzes primary sources from the Qur’an and Hadith, alongside classical and contemporary scholarly works, to construct a conceptual framework of tauhid-based education. Findings indicate that tauhid functions as a unifying paradigm, preventing value fragmentation and guiding educational practices that balance intellectual competence, moral integrity, and spiritual awareness. In contemporary contexts, its integration addresses challenges such as secularization, knowledge compartmentalization, and moral-spiritual crises. Embedding tauhid in educational philosophy provides a normative and practical foundation to cultivate students who are knowledgeable, ethical, and spiritually grounded, ensuring Islamic education remains holistic, relevant, and sustainable.